The posadsky wife Matrona Kalistratova in the history of Church and book culture of the Kostroma region of the 17th century - Yu. S. Belyankin (Российский журнал истории Церкви)
In the article a source study of inscriptions on Cyrillic books of the 17th century was carried out, as a result of which it was possible to uncover a rare historical plot, the main character of which is one of the notable residents of the city of Soligalich at the time. We are talking about the book contributions of the posadsky wife Matrona Kalistratova, a wealthy owner of salterns аnd other property, that have survived to date. Her book donations, addressed to Soligalich and the nearby Gorodets monastery, made it possible to highlight some facts from Matrona’s biography and her role in the Church history of the Kostroma Region. It turned out that Matrona Kalistratova is one of the participants in the posthumous miracles of St. Abramius of Galich, which is reflected in the Life of the saint. It is the detailed inscriptions on her book contributions, which immediately attract attention due to their content among the preserved old printed books of the Kostroma Region repositories, that allowed us to draw undoubted parallels with the hagiographic text. Mutually complementing each other, the Life of St. Abramius of Galich, archival data and book descriptions clarified various details from the life of Matrona Kalistratova and her trace in the book culture of the Kostroma lands in the second third of the 17th century. The relatively large book contribution of the posadsky wife is a remarkable phenomenon in itself, as well as the fact that it became a commemoration that recorded the miraculous healing of the depositor on the relics of the saint.